Design, synthesis, and biological evaluation of substituted benzyl-triazolopyridine derivatives as non-hydroxamate based HDAC8 inhibitors - N.V.M. Rao Bandaru; Ashna Fathima; Vandana Joshi; Markus Schweipert; Obanna Pathur; Kosana Sai Chaitanya; Trinath Jamma; Vivek Sharma; Chandrasekhar Abbineni; Franz-Josef Meyer-Almes; Kondapalli Venkata Gowri Chandra Sekhar (European Journal of Medicinal Chemistry Reports)
Traditional Histone deacetylase 8 (HDAC8) inhibitors primarily rely on hydroxamate-based scaffolds. However, there is a growing interest in developing non-hydroxamate inhibitors to overcome potential limitations with hydroxamate-based inhibitors. In this study, we report the design, synthesis, and evaluation of a series of benzyl-1,2,4-triazolo [4,3-a] pyridine derivatives as non-hydroxamate HDAC8 inhibitors. Their HDAC8 inhibitory activities were assessed by enzymatic assay. Active compounds from the HDAC8 enzymatic assay were evaluated in various cancer cell lines, revealing that compound 9i demonstrated significant anti-neuroblastoma activity. Docking studies on compound 9i were conducted to explicate its structural basis. The additional experiments showed that compound 9i inhibited colony formation, induced hyperacetylation of SMC3, suppressed cell migration, triggered apoptosis, and caused cell cycle arrest in IMR-32 neuroblastoma cells. Overall, these inhibitors showed promising activity and a strong correlation with observed phenotypic effects, suggesting their potential for further development as therapeutic agents for cancer treatment.